PENGEMBANGAN MODUL PEMBELAJARANPADA POKOK BAHASAN IDENTIFIKASI KANDUNGAN MATERIALBERBASIS RISET DAN KEARIFAN LOKAL - Pangga, Dwi; Prasetiya, Dwi Sabda Budi (Lensa : Jurnal Kependidikan Fisika, 2016)
This study aims to develop a 'learning module' identification of material content based on research and local wisdom. This module is a refinement of the Material Physics module. This course is an option; therefore the content tends towards the development of talent and interest to motivate the Master's degree. During this study more based on literature studies, the means are very limited. As a result, many curiosity and student awareness can not be missed because learning through research is very limited. The development of research-based modules and local wisdom can support the needs of students to conduct research. The research method used in this research is R & D research using Borg & Gall development model including product analysis, development, expert validation and revision, small field trial phase, large scale field trial and final product result. Learning module on subject matter identification of research-based materials and local wisdom as a product of development.